Upaya United Nations Women Terhadap Kekerasan Perempuan pada Pandemi Covid-19 (Shadow Pandemic) di Indonesia - Viola Marsela Agustin; Maria Veri Diana Baun Yuel; Ariel Nethan; Ananda Dewin Ikhtiarin; Yeyen Subandi (Yayasan Literasi Sains Indonesia, 2023)
This research is motivated by the rampant sexual violence that occurs against women in Indonesia during the COVID-19 Pandemic. The existence of the COVID-19 Pandemic has created a shadow Pandemic, namely the increasing number of sexual violence against women. This then attracted the attention of an international organization, namely UN Women. UN Women called this phenomenon “The Shadow Pandemic” and implemented policies to save women from this crisis. This research is based on the theory of international organizations and women's empowerment which is the main focus of UN Women. The purpose of this research is to analyze the application of UN Women's policies on sexual violence against women in Indonesia. In this study the authors used qualitative observation research methods. Qualitative observations will result from data interpretation by providing analysis and description. The results of this study indicate that in the midst of the COVID-19 Pandemic, it has caused many problems for human life throughout the world, especially for the people of Indonesia. These problems include psychological, economic, social suffering, and have even led to